Julian, first published woman writer in English - Hasan, Md. Mahmudul (The University of Portsmouth, UK, 2019)
Even though Julian is not widely discussed, her influence on literary successors is remarkable. Two lines in T. S. Eliot’s “Burnt Norton” (1936) – “Except for the point, the still point, / There would be no dance and there is only the dance” (ll.20-21) – are a clear allusion to Julian’s statement: “I saw God in a point by which vision I understood that He is in all things.” Robert Browning’s belief “God’s in his heaven – / All’s right with the world!” echoes Julian’s devotional optimism: “All shall be well, and all shall be well, and all manner of things shall be well.” She is known to have influenced many other writers of the past and present.